Toward a Theory of Student Aspirations - Russell J. Quaglia; Casey D. Cobb (Journal of Research in Rural Education, 1996)
Student aspirations is a term that is usedfrequently in education, yet there is little understanding and agreement as to what it means and even less understanding about its origin. It is the purpose of this paper to trace some of the key historical perspectives ofthe construct ofaspirations, and from this backdrop introduce a new manner in which to view student aspirations. We have elected here to highlight two influential areas ofresearch: level ofaspiration and achievement motivation. These key areas, supplemented by social comparison theory, provide a historicalframework with which to understand aspirations.